Development of an Enzyme-Linked Immunosorbent Assay Method for the Detection of Rhein in Rheum officinale. (16th March 2020) - Chen, Min; Nan, Tie-Gui; Xin, Jie; Cui, Li; Zhang, Bo; Wang, Xiao; Wang, Bao-Min
Abstract : Rhein is an important quality-control marker of Rheum officinale . The aim of this study was to develop an indirect competitive enzyme-linked immunosorbent assay (icELISA) for rhein detection, which acts as a powerful tool for quality control and proper usage of Rheum officinale . First, a specific and sensitive monoclonal antibody (mAb) against rhein was produced from a stable hybridoma cell line, 1F8, generated by the fusion of mouse myeloma sp2/0 with spleen cells obtained from a Bal b/c mouse immunized with rhein-BSA. Then, an icELISA method was developed with an IC50 value and working range of 0.05 μ g L −1 and 0.02–0.11 μ g L −1, respectively. The icELISA revealed high assay specificity, since it only had a relatively high cross reactivity with aloe-emodin (27%) and almost no cross reactivity with any other anthraquinones (<1%). When spiked with 0.2–2 mg kg −1 of rhein, the recoveries ranged from 84.19% to 102.90%. Finally, icELISA was used to detect rhein contents of Rheum officinale collected from different regions, and the results corresponded well with those of HPLC. Overall, the developed icELISA with high specificity and sensitivity provided a rapid and simple method for rhein detection, and it may be a powerful tool for quality control and proper usage of Rheum officinale .